Peran Dan Kompetensi Auditor Syariah Dalam Menunjang Kinerja Perbankan Syariah - Aulia Putri Oktaviani Jusri; Erina Maulidha (JAS (Jurnal Akuntansi Syariah), 2020)
The increase in the growth of Islamic banking needs to be supported by the performance of sharia auditors. This study aims to discuss the role and competence of Islamic auditors in supporting the performance of Islamic banking. This type of research uses qualitative methods with a descriptive approach using literature study data. The results of this study indicate that the competencies that must be possessed by sharia auditors include knowledge of Islamic law, fiqh muamalah, skills in accounting and auditing, and special characteristics as sharia auditors. This competence is the key to maximizing the role and competence of sharia auditors to support the performance of Islamic banking. The roles of sharia auditors include as independent auditors, internal auditors, and sharia supervisory board. Sharia compliance tests on Islamic financial institutions are part of the role of the sharia auditor.